Fungsi Seni Pertunjukan Wayang Kulit Bali Lakon Bhima Swarga dalam Upacara Yadnya - Sugita, I Wayan; Tilem Pastika, I Gede (Jayapangus Press, 2022)
Balinese performing arts, especially Balinese shadow puppet performances, are closely related to the implementation of the Yadnya ceremony. Not only in terms of the form of the performance, but also in the context of the functions presented by the Balinese shadow puppet performance. The story used is a part that is always integrated with the context and type of Yadnya. Mahabharata is one of the play guidelines used, but The Dalang (Puppet Master) often improvises the story to suit the needs of the show. One of the improvised stories from the Mahabharata is the story of Bhima Swarga. The story of Bhima Swarga is closely related to the purification of ancestral spirits and Pitra Yadnya. However, the public does not know much about the function of the Balinese shadow puppet performing art Bhima Swarga's story, therefore it is interesting to study to know the functions contained in the Balinese shadow puppet performance art of Bhima Swarga's story. The method used is qualitative descriptive. This research was conducted centrally in Sukawati Village, Sukawati District, Gianyar Regency. The results showed that the Balinese shadow puppet performance art Bhima Swarga's story has a function as 1) complementary ritual is seen from the use of sacred puppets, ritual ceremonies, and making tirtha. 2) the function of religious education, improving sraddha through dialogue, and storytelling. 3) creativity in art 4) entertainment, and 5) economic function